PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING AND EXTENDING) TERHADAP HASIL BELAJAR SISWA KELAS X - Andi Trisnowali; Andi Aswina (Didaktika : Jurnal Kependidikan, 2019)
This study aims at determining the influence of the CORE (Connecting, Organizing, Reflecting, and Extending) Learning model on the students’mathematics learning outcomes at grade X SMA 5 Watampone. The research design used was posttest only control design (posttest subjects only control group design). This research was conducted at SMA 5 Watampone. The population was all students at class X and the samples were randomly selected; students at XII-2 and XII-3 classes. Data on learning outcomes obtained through posttest. Data is processed using the t-test. The results of data analysis indicated that the experimental class obtained an average value of learning outcomes (mean) is 85.28, the standard deviation (standard deviation) is 9.110, the variance is 82.993 and the standard error is 1.692, while in the control class the mean is 75.66, standard deviation 8,703, variance 75,734, and standard error mean 1,616. It is concluded that "there is influence of the CORE Learning model on the students’mathematics learning outcomes at grade X SMA 5 Watampone.Keywords: CORE Learning Models, Mathematics Learning Outcomes.